Formação continuada docente: atuação da coordenadoria sociopedagógica no instituto federal de educação, ciência e tecnologia de São Paulo - Costa, Roseli Gomes de Lima (2018)
This study takes a pedagogical challenges faced by the Sociopedagogical Coordination (CSP) of the Federal Institution of Education, Science and Technology of the State of São Paulo (IFSP) – São Roque Campus. As the focus of the research, the continuing teacher formation for the professional and technological education (EPT) of the IFSP and how does this teaching relation in the class of Technical Education Integrated with High School (ETIM), considering this is a specific teaching model, which brings together in a single class the professional training and the general training and, consequently, have a more complex curriculum than a subsequent technical class. To this end, discusses its multidisciplinary structure, that highlight for its scope to achieve, inside of the same institution and at the same time, since the basic education until the post-graduation studies, in a scenario that the institution’s teachers face the challenge of attending to the various levels of education. Seeks out, through this research, reflect about the difficulty of CSP performance, through the continuing teacher education and the imposed conflicts by the teaching profession, in face of the specifics of the technical class. As the ultimate objective of this research, is the contribution in the construction of subsidies for CSP action strategies, focusing on the IFSP’s ETIM class, at the São Roque Campus. In order to understand the interconnected aspects to continuing training and its methodologies resorted to António Nóvoas, Maurice Tardif, Richard Wittorski’s studies, among others. The research used data collection, questionnaire application and semi-structured interviews with teachers of ETIM’s class and to the continuing training team of São Roque Campus. For interview analysis, was adopted the content analysis. The results showed that the monthly pedagogical meetings to continuing education at São Roque Campus are a punctual source of reflection on pedagogical practice. However, the distance between teachers and CSP in Campus daily life, appear as a concern and cause of difficulty in the execution of actions of this training.